2017
DOI: 10.1108/jieb-08-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Does accumulated knowledge impact academic performance in cost accounting?

Abstract: Purpose This quantitative study aims to examine the impact of accumulated knowledge of accounting on the academic performance of Cost Accounting students. Design/methodology/approach The sample consisted of 89 students enrolled in the Accounting program run by a business college in Kuwait during 2015. Correlation and linear least squares regression analyses tested the study’s hypothesis. Findings Results indicated significant impact of accumulated knowledge on academic performance, with and without control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
4
0
4
Order By: Relevance
“…Seow et al (2014) reported that prior academic achievement, admission interview, critical thinking, and mathematical aptitude were significantly associated with successful academic performance in an undergraduate accounting degree at a Singapore University. Alanzi and Alfraih (2017) found that accumulated quantitative knowledge has positive impact on academic performance in Cost Accounting; however, Gist et al (1996) did not report the same results. Furthermore, Guney (2009) suggested that grades in secondary education mathematics are a very strong determinant of performance in accounting but only for non-accounting majors.…”
Section: Introductionmentioning
confidence: 94%
“…Seow et al (2014) reported that prior academic achievement, admission interview, critical thinking, and mathematical aptitude were significantly associated with successful academic performance in an undergraduate accounting degree at a Singapore University. Alanzi and Alfraih (2017) found that accumulated quantitative knowledge has positive impact on academic performance in Cost Accounting; however, Gist et al (1996) did not report the same results. Furthermore, Guney (2009) suggested that grades in secondary education mathematics are a very strong determinant of performance in accounting but only for non-accounting majors.…”
Section: Introductionmentioning
confidence: 94%
“…Existen indicios de que los conocimientos acumulados en asignaturas contables previas y en matemáticas tienen incidencia directa en el rendimiento de los estudiantes de Contabilidad de Costos, que podría estar sugiriendo que la Teoría General Contable de alguna manera impacta en el análisis de costos. Pero, al mismo tiempo, también hay autores que indican que la escolaridad previa general -y no exclusivamente la contable-es también determinante del rendimiento en materia de contabilidad de costos (Alanzi, 2015;Alanzi y Alfraih, 2017;Al-Twaijry, 2010).…”
Section: Marco Teórico Y Antecedentesunclassified
“…En definitiva, se habría podido utilizar el mismo estado contable, pero identificando por separado la unidad de negocios exportadora del caso analizado. Estos resultados son coherentes con la literatura cuando se advierte de indicios de que los conocimientos acumulados en contabilidad tienen incidencia directa en el rendimiento de los estudiantes de Contabilidad de Costos (Alanzi y Alfraih, 2017).…”
Section: Gráfica 1 Distribución De Calificacionesunclassified
“…For students that adopt deep approaches to learning, analytical and conceptual thinking skills are more likely to develop, which in turn promote stronger academic performance (Ginns, Martin, & Papworth, 2018;Hall, & Raven, 2004). In a business studies context, several studies (Abhayawansa, Bowden, & Pillay, 2017;Alanzi & Alfraih, 2017;Davidson, 2003) found that deep learning increases academic performance, whereas surface learning does the opposite. The latter is also confirmed by Fryer and Ginns (2018) and Teixeira and Gomes (2017).…”
Section: Motivation Learning Approaches and Academic Performancementioning
confidence: 99%